Examination of how a settlement on the Great Plain became a town, with a special regard to its present and future - Gál, József; Bódi, Brigitta Mária; Nagy, Sándor; Kovács, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
We are aiming to describe the process how Sándorfalva was declared a town, its economic, social, infrastructural conditions, its level and the course of development.We are seeking answers to these questions: what possibilities, risks, weak and strong points does this settlement have? What is the future strategy of this town, and how does it intend to realize it? We have two important conclusions here. The first one is that it is the human factor which is in the centre of development, so we are emphasizing the importance of collaboration, the other one is the formation of competitiveness which can result in a town of European level.